Pengaruh Current Ratio dan Debt to Equity terhadap Harga Saham, dengan Return on Equity dan Return on Assets sebagai Variabel Intervening (Studi Kasus pada Perusahaan Food and Beverages yang Terdaftar di BEI pada Periode 2013-2017) - Nana Adnan Rahmanto; Ngatno Ngatno (Universitas Diponegoro, 2018)
The purpose of this research is to analyze the effect of CR and DER on stock price with ROE and ROA as intervening variable in food and beverages companies listed in BEI period 2013 - 2017. CR represents liquidity ratio, DER represents leverage ratio ROE and ROA represent profitability ratios. Stock Price used in this research is the closing price. This research uses quantitative method and explanatory research type. In this research there are 8 companies taken as research unit. The data in this research were taken from IDX. Data analysis in this study used multiple linear regression analysis and sobel test used to test the influence of mediation from intervening variable. The results of this research show that in partial CR and DER have a significant effect to ROE. CR have a significant effect to ROA, while DER have an effect and not significant to ROA. CR, ROE and ROA have a significant effect on Stock Price, while DER have an effect and not significant to Stock Price. The test results of the influence of mediation, ROE and ROA can mediate the effect of CR on Stock Price significantly. Then ROE and ROA can mediate the effect of DER on Stock Price but not significant.